Size-dependent bending modulus of fibre composite laminates comprising unidirectional plies. (November 2021) - Nourmohammadi, Nastaran; O'Dowd, Noel P.; Weaver, Paul M.
Abstract: Heterogeneous materials can show size-dependent behaviour in which the bending modulus depends on sample size. In fibre composite materials the interaction between fibre and matrix can lead to such a size effect.Then the effective modulus calculated by the rule of mixtures can either underestimate or overestimate the bending modulus of the laminate, depending on the fibre/matrix material mismatch, the microstructural morphology (fibre distribution) and the laminate thickness. In this work, the bending behaviour of a laminate comprising unidirectional fibre composite plies is considered using Euler-Bernoulli beam theory and the influence of size on the bending modulus is investigated. The effective bending modulus of each ply is calculated and used to formulate the overall bending modulus of the laminate. The results show that the laminate bending modulus depends on the number of plies, the number of fibres through the thickness of each ply, the fibre spacing and radius, and the mismatch of fibre and matrix material properties in each ply. Our analysis shows that accounting for the ply microstructure (fibre spacing and radius and number of fibres per ply) can lead to a 10% difference in the predicted bending modulus in a three ply laminate, when there are less than four fibres through the thickness in each ply.